Advances in Informatics and Computing in Civil and Construction Engineering Proceedings of the 35th CIB W78 2018 Conference: IT in Design, Construction, and Management - Mutis, Ivan.; Hartmann, Timo.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This proceedings volume chronicles the papers presented at the 35th CIB W78 2018 Conference: IT in Design, Construction, and Management, held in Chicago, IL, USA, in October 2018. The theme of the conference focused on fostering, encouraging, and promoting research and development in the application of integrated information technology (IT) throughout the life-cycle of the design, construction, and occupancy of buildings and related facilities. The CIB - International Council for Research and Innovation in Building Construction - was established in 1953 as an association whose objectives were to stimulate and facilitate international cooperation and information exchange between governmental research institutes in the building and construction sector, with an emphasis on those institutes engaged in technical fields of research. The conference brought together more than 200 scholars from 40 countries, who presented the innovative concepts and methods featured in this collection of papers. Some of the papers' topics included the following: • Virtual, augmented, and mixed reality • Visualization and simulation • Communication and collaboration informatics • Sensor data interpretation • Situation awareness and sensing technologies • Mobile computing • Geometric and parametric modeling • Building information modeling (BIM) • 4-D/n-D modeling • Computer-enhanced engineering design • Design and decision support systems • Ontologies and reasoning for civil and construction engineering • Semantic modeling in the AEC industry • Product and process modeling • Data acquisition, analysis, and storage.
Computing and Innovations for Design Sustainable Buildings and Infrastructure -- Thermal Performance Assessment of Curtain Walls of Fully Operational Buildings Using Infrared Thermography and Unmanned Aerial Vehicles -- BIM and Lean-Business Process Reengineering for Energy Management Optimization of Existing Buildings -- Geographic Information Systems (GIS) based visual analytics framework for highway project performance evaluation -- Usage of Interface Management in adaptive reuse of buildings -- Semantic Enrichment of As-is BIMs for Building Energy Simulation -- Proof of Concept for a BIM-based Material Passport -- Learning from Class-Imbalanced Bridge and Weather Data for Supporting Bridge Deterioration Prediction -- Machine-Learning-Based Model for Supporting Energy Performance Benchmarking for Office Buildings -- Occupants Behavior-based Design Study Using BIM-GIS Integration: An Alternative Design Approach for Architects -- Standardisation of Whole Life Cost estimation for early design decision-making utilising Building Information Modelling -- Data Model Centered Road Maintenance Support System Using Mobile Device -- Ontology-based Semantic Modelingof Disaster Resilient Construction Operations: Towards a Knowledge-based Decision Support System -- A methodology for real-time 3D visualization of asphalt thermal behavior during road construction -- Eliminating Building and Construction Waste with Computer-Aided Manufacturing and Prefabrication -- A methodological proposal for risk analysis in the construction of tunnels -- Technology Alternatives for Workplace Safety Risk Mitigation in Construction: Exploratory Study -- Part 7. Education, Training, and Learning with Technologies -- BIM4VET, towards BIM training recommendation for AEC professionals -- Teaching effective collaborative information delivery and management in response to a BIM mandate -- A Story of Online Construction Masters' Project: Is An Active Online Independent Study Course Possible? -- Lessons learned from a multi-year initiative to integrate data-dri.
Keywords: Buildings -- Design and construction; Data mining; Buildings -- Repair and reconstruction; Buildings -- Maintenance; Computer-aided engineering; Light construction; Steel construction; Lightweight construction; Construction industry -- Management; Building Construction and Design; Data Mining and Knowledge Discovery; Building Repair and Maintenance; Computer-Aided Engineering (CAD, CAE) and Design; Light-weight Construction, Steel and Timber Construction; Construction Management